PENGGUNAAN WARNA DALAM KONTEKS CATAN "SUNSET" DAN "SUNRISE" BERDASARKAN KEPADA KARYA J.M.W TURNER DAN CLAUDE MONET - Jong, Teng Teng. (unimas, 2017)
This article explains the research on colours and other factors in the context of "sunset" and "sunrise" based on the work of J. M. W Turner and Claude Monet. The researcher chose several works of J. M. W Turner and Claude Monet that provides historical insights. This research paper clearly depicts the significant colours used by J. M. W Turner and Claude Monet with analysis of other factors within this context. The end of the research identifies the contextualized usage of colour with other factors. This research paper serves as a reference platform and a source of inspiration that applies in the personal artwork.